2015
DOI: 10.1159/000381659
|View full text |Cite
|
Sign up to set email alerts
|

Oral Propranolol: A New Treatment for Infants with Retinopathy of Prematurity?

Abstract: interventional studies are required to determine the clinical benefit-risk ratio of oral propranolol to prevent vision-threatening ROP in very preterm infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Studies have shown that polymorphisms of the β-adrenergic receptor in many black infants may be responsible for the lower incidence of ROP (107). Clinical trials have shown reduction in the incidence of ROP with oral propranolol with few side effects (108)(109)(110). Clinical trials in Israel and Italy are being conducted to evaluate efficacy and safety of this beta blocker for ROP prevention in preterm neonates.…”
Section: Propranololmentioning
confidence: 99%
“…Studies have shown that polymorphisms of the β-adrenergic receptor in many black infants may be responsible for the lower incidence of ROP (107). Clinical trials have shown reduction in the incidence of ROP with oral propranolol with few side effects (108)(109)(110). Clinical trials in Israel and Italy are being conducted to evaluate efficacy and safety of this beta blocker for ROP prevention in preterm neonates.…”
Section: Propranololmentioning
confidence: 99%
“…Oral propranolol (0.25 or 0.5 mg/kg/6 h) was given in a pilot trial to preterm infants with stage 2 ROP during phase II ROP [54] and the authors concluded that the drug was effective in decreasing the progression of ROP but that safety was a concern. Recently, there have been two small randomized controlled trials of oral propranolol as a treatment for stage 2 or more (zone 2) ROP or stage 1 (zone 1) ROP [55]. These trials had unclear methodology, but 6 infants with ROP interventions from 35 propranolol-treated infants compared to 14 out of 36 control infants (p = 0.055, relative risk 0.44, 95% CI: 0.19-1.02) translates to a number needed to treat of 5.…”
Section: New Therapeutic Options For Ropmentioning
confidence: 99%
“…These trials had unclear methodology, but 6 infants with ROP interventions from 35 propranolol-treated infants compared to 14 out of 36 control infants (p = 0.055, relative risk 0.44, 95% CI: 0.19-1.02) translates to a number needed to treat of 5. Oral propranolol is a promising treatment to prevent progression to threshold ROP, but systematic studies are needed before it can be recommended [55]. A trial of propranolol during phase I to prevent ROP in infants with gestation of 26-32 weeks starting at 1 week of age and continuing until 37 weeks or complete vascularization of retina is ongoing (CTRI/2013/11/004131).…”
Section: New Therapeutic Options For Ropmentioning
confidence: 99%
“…These studies demonstrated a lesser progression to stage 3 or stage 3 plus. Combining the published data of the trials by Filippi et al 7 and Makhoul et al 15 would result in 6 infants needing ROP interventions out of 35 propranolol-treated infants, as opposed to 14 out of 36 control infants (p=0.055, RR 0.44, 95% CI 0.19 to 1.02, relative density (RD) 0.22, number needed to treat (NNT)=5) 18. Though the study of Bancalari et al 16 showed a decrease in the need for intervention with laser or bevacizumab in the study group, it was not a randomised controlled study.…”
Section: Discussionmentioning
confidence: 99%